2010
DOI: 10.18806/tesl.v27i2.1054
|View full text |Cite
|
Sign up to set email alerts
|

Corrective Feedback for Learners of Varied Proficiency Levels: A Teacher’s Choices

Abstract: This study investigates how one English-as-a-second-language (ESL) teacher provided corrective feedback to 15 child ESL learners that the teacher had divided into two groups based on proficiency level. Classroom data in transcripts from the CHILDES database were analyzed for type of learner errors, type of teacher feedback, and rate of learner uptake (attempts at correction) and repair (correction). Results showed differences in the types of errors produced by each proficiency group and in the type of feedback… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 16 publications
2
18
1
Order By: Relevance
“…Corrective feedback includes the implicit provision of target language forms (i.e., recast), techniques for selfcorrection (i.e., clarification request, metalinguistic feedback, elicitation, and repetition), and explicit error correction techniques (Lyster & Ranta, 1997;Panova & Lyster, 2002;Sheen, 2004). Findings on corrective feedback in EFL classrooms (Ahangari & Amirzadeh, 2011;Kennedy, 2010;Panova & Lyster, 2002;Sheen, 2004) indicate that recast (when the teacher implicitly reformulates the student's error, or provides the correction) is the predominant technique that teachers employ, even though it leads to the lowest rate of uptake of the target language. In comparison, techniques that encourage student selfresponses, such as clarification requests, metalinguistic feedback (when the teacher poses questions related to the formation of a student's utterances), elicitation (when the teacher directly elicits the correct form from the student by asking questions, pausing, or asking for correction), and repetition, lead to more successful student-generated repair (J.…”
Section: Introductionmentioning
confidence: 99%
“…Corrective feedback includes the implicit provision of target language forms (i.e., recast), techniques for selfcorrection (i.e., clarification request, metalinguistic feedback, elicitation, and repetition), and explicit error correction techniques (Lyster & Ranta, 1997;Panova & Lyster, 2002;Sheen, 2004). Findings on corrective feedback in EFL classrooms (Ahangari & Amirzadeh, 2011;Kennedy, 2010;Panova & Lyster, 2002;Sheen, 2004) indicate that recast (when the teacher implicitly reformulates the student's error, or provides the correction) is the predominant technique that teachers employ, even though it leads to the lowest rate of uptake of the target language. In comparison, techniques that encourage student selfresponses, such as clarification requests, metalinguistic feedback (when the teacher poses questions related to the formation of a student's utterances), elicitation (when the teacher directly elicits the correct form from the student by asking questions, pausing, or asking for correction), and repetition, lead to more successful student-generated repair (J.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is linear to Kennedy's (2010) study, indicating that grammatical errors are the most frequently committed errors by the learners. Conversely, Sung & Tsai's (2014) investigation revealed that grammatical errors are rarely made errors by the Chinese EFL learners, although there is substantial difference existing between Chinese grammar and English grammar.…”
Section: Discussionmentioning
confidence: 55%
“…Furthermore, Ahangari and Amirzadeh's (2011) findings are in line with Kennedy's (2010).Specifically, they explored teachers' provided CF to learners at different proficiency levels. Whereas the most frequent type of CF in all three levels was recast, the frequency of using it reduced as the learners became more proficient.…”
Section: International Journal Of Linguisticsmentioning
confidence: 78%
“…More recently, Kennedy (2010) carried out a study to investigate young learners' type of ISSN 1948-5425 2016 www.macrothink.org/ijl 154 error in two different levels of proficiency and also their teachers' preferred CF practices. The findings revealed that low-proficiency learners made more content errors, whereas the high-proficiency students made more form errors.…”
Section: Review Of Studiesmentioning
confidence: 99%